Isolation and identification of the indigenous yeast population during spontaneous fermentation of Isabella (Vitis labrusca L.) grape must - Raymond Eder, María Laura (2017)
Grape must harbors a complex community of yeast species responsible for spontaneous alcoholic fermentation. Although there are detailed studies on the microbiota of Vitis vinifera L. grapes, less is known about the diversity and behavior of yeast communities present on fermenting grape must from other species of Vitis. In this work, we used a culture-dependent method to study the identity and dynamics of the indigenous yeast population present during the spontaneous fermentation of Isabella (Vitis labrusca L.) grape must. Alcoholic fermentation was conducted using standard enological practices, and the associated non-Saccharomyces and S. cerevisiae yeast community was analyzed using selective growth media and 5.8-ITS DNA sequencing. Candida californica, Candida hellenica, Starmerella bacillaris (synonym Candida zemplinina), Hanseniaspora uvarum, and Hanseniaspora vineae were the main non-Saccharomyces species identified on Isabella fermenting must. Issatchenkia hanoiensis, a yeast species rarely found on Vitis vinifera L. grapes, was also recognized on Isabella grape must. Candida azymoides, Candida californica and Pichia cecembensis, identified in this work on Isabella fermenting must, have not previously been found on Vitis vinifera L. grape must. Interestingly, C. azymoides, I. hanoiensis and P. cecembensis have recently been isolated from the surface of Vitis labrusca L. grapes from vineyards in the Azores archipelago, suggesting that specific Vitis-yeast species associations are formed independently of geographic origin. We suggest that C. azymoides, C. californica, and P. cecembensis are yeast species preferentially associated with Vitis labrusca L. grapes. Specific biological interactions between grapevines and yeast species may underlie the assembly of differential Vitis-microbial communities.